Quo Vadis Mahkamah Konstitusi: Telaah Politik Hukum Revisi Ketiga Undang-Undang Mahkamah Konstitusi - Yudha Agung Pratama; Imam kadir (Journal Law and Government, 2025)
Along with the enactment of Law Number 7 of 2020 concerning the Third Amendment to Law Number 24 of 2003 concerning the Constitutional Court (Constitutional Court Law) which has reaped academic and practical debates among the public, especially regarding its urgency aspects towards strengthening the independence of the constitutional justice institution, so this study is present to identify the nature and characteristics of the dynamics of the formation of the third revision of the Constitutional Court Law which is analyzed parsimoniously in the legal political landscape. This study is a normative legal research conducted through a library research method using several approaches, namely the statute approach, conceptual approach and case approach. The results of the study show that the strengthening of the government's position and the weakening of the role of the DPR as well as civil society in the third revision of the Constitutional Court Law as a result of the formation of an oversized coalition posture have implications for legislative performance that characterizes the authoritarian political configuration. Then, the massive public criticism of the norms in the third revision of the Constitutional Court Law, which in fact is considered not in line with public aspirations, substantively indicates that the law produces conservative legal arrangements.